Hemodynamics and Gas Exchange Effects of Inhaled Nitrous Oxide in Patients with Acute Respiratory Distress Syndrome - V. N. Poptsov (Общая реаниматология)
Inhaled nitrous oxide (iNO) therapy aimed at improving pulmonary oxygenizing function and at decreasing artificial ventilation (AV) load has been used in foreign clinical practice in the past decade. The study was undertaken to evaluate the hemodynamic and gas exchange effects of iNO in acute respiratory distress syndrome (ARDS) that developed after car-diosurgical operations. Fifty-eight (43 males and 15 females) patients aged 21 to 76 (55.2±2.4) years were examined. The study has demonstrated that in 48.3% of cases, the early stage of ARDS is attended by the increased tone pulmonary vessels due to impaired NO-dependent vasodilatation. In these patients, iNO therapy is an effective therapeutic method for correcting hemodynamic disorders and lung oxygenizing function.